ANALISIS PEMASARAN ABON IKAN TUNA (Thunnus sp) DI KOTA BONTANG KALIMANTAN TIMUR - Nisyak, Aliyyatun; Purnamasari, Elly; Abdusysyahid, Said (PAKIS JOURNAL INSTITUTE, 2024)
This research aims to analyze the marketing efficiency of tuna fish floss in Bontang City with a focus on distribution channels and marketing costs. The research method used is qualitative, quantitative using questionnaires to conduct structured interviews. Data sample collection is determined by census and snowball sampling, then analyzed descriptively and calculating margins, profits, farmer's share of business costs. The 4 marketing institutions involved produced 2 marketing channel patterns, namely level 0 marketing channels and level 1 marketing channels. The highest margin was obtained by Habati and Borena's roasted processed floss, namely IDR. 6,000 per pack. Likewise with profits, roasted floss (15,936) is greater than fried floss (13,844). The average value of the farm's share was 77.79%. Marketing of tuna fish floss in Bontang City is quite efficient, judging from the results of the discussion found. Suggestions for the development of floss marketing from researchers include developing more diverse flavor variants of processed tuna floss, improving promotional designs for good nutritional value on product packaging. and forming collaborative partners with retail traders that are more structured, such as promotional permits using intermediary trader contact persons, so that it is profitable for both parties. Retailers gain the trust of end consumers and can order more from manufacturers.